Implementasi Konsep Wisata Berbasis Masyarakat sebagai Usaha Pemberdayaan Masyarakat Muara Gembong - Hapzi, Hapzi; Untari, Dhian Tyas; khasanah, Fata Nidaul (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2024)
Community-Based Tourism (CBT) is a tourism approach that emphasizes the active role of local communities in managing tourist destinations to create sustainable economic, social, and environmental benefits. This article discusses the concept, principles, impacts, challenges, and implementation of CBT, focusing on a case study in Muara Gembong. Muara Gembong has great potential in mangrove ecotourism, marine tourism, and agro-tourism, which can be developed through a community-based approach. Research shows that the success of CBT in Muara Gembong depends on assistance, infrastructure improvements, and collaboration between the community, government, and private sector. With the right strategy, Muara Gembong can become a successful model for CBT development in Indonesia.